Correlation Of Self-Regulation And Learning Habits With Student's Thesis Writing Skills - Jinorid Misa; Agustinus Maniyeni; Maglon Ferdinand Banamtuan (Jurnal Pendidikan Agama Kristen (JUPAK), 2022)
This study aims to determine the correlation between self-regulation and study habits with thesis writing skills of students at the Kupang State Christian Institute. The study used a quantitative approach with the correlational method. The population in this study amounted to 248 people consisting of semester IX students, while the research sample amounted to 71 people who were calculated using the Slovin formula. Data was collected through distributing questionnaires and then continued with carrying out data processing using statistical techniques. Based on the results of the correlation analysis of the three variables, the coefficient price of 0.311 is obtained, it can be said that between the variables X1 and X2 with Y has a significant correlation, then from the analysis results also obtained the coefficient of determination (r-square) of 0.097 or equivalent to 9, 7%. This means that the correlation between self-regulation and study habits with thesis writing skills for students of the State Christian Institute of the State Christian Institute of Kupang is 9.7% and the remaining 90.3% is caused by other factors outside the variables of self-regulation and study habits. . From these results, the researcher can draw the conclusion that the alternative hypothesis (Ha) is accepted.